2007
DOI: 10.1007/s10529-007-9378-6
|View full text |Cite
|
Sign up to set email alerts
|

Lisosan G, a powder of grain, does not interfer with the drug metabolizing enzymes and has a protective role on carbon tetrachloride-induced hepatotoxicity

Abstract: Lisosan G is a powder of grain registered as an alimentary integrator. The treatment of rats for 4 days with 0.5 g Lisosan G/kg had no effect on various drug metabolizing enzymes. Experiments in vitro showed that Lisosan G had radical scavenger activity. A confirmation of the antioxidative property of Lisosan G was also confirmed when it was administered in vivo to carbon tetrachloride (CCl(4))-intoxicated rats. The toxicity caused by CCl(4)-treatment of rats was restored to the control levels when the rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
4
26
0
1
Order By: Relevance
“…However, the bilirubin level decreased slightly in the Lisosan G fed rabbits. The results on the lack of hepatoxicity of Lisosan G confirmed the results of a previous study on rats, in which a protective role of carbon tetrachlorideinduced hepatotoxicity was observed (Longo et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, the bilirubin level decreased slightly in the Lisosan G fed rabbits. The results on the lack of hepatoxicity of Lisosan G confirmed the results of a previous study on rats, in which a protective role of carbon tetrachlorideinduced hepatotoxicity was observed (Longo et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The antioxidant activity of Lisosan G was previously evaluated through in vitro and in vivo experiments (Longo et al, 2007;Frassinetti et al, 2012;La Marca et al, 2013;Longo et al, 2014). Frassinetti et al (2012) demonstrated that Lisosan G removed the free radicals that originated from a normal aerobic metabolism and increased CAT, glutathione peroxidase (GPX) and superoxide dismutase (SOD).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations